Stress Analysis of Negative Coal Pillar Gob-Side Entry and Its Principle of Preventing Rock Burst - Zhiqiang Wang; Peng Wang; Lei Shi; Wenyu Lv; Chao Wu; Jianqiao Luo (Shock and Vibration)
Gob-side entry is an area where it is difficult to prevent and control the frequent occurrence of rock burst. Based on “Longwall Mining with Split-level Gateways” (LMSG), this paper puts forward the technology of preventing rock burst by a new gob-side entry (NCPG). The abutment pressure distribution of LMSG shows that the stress peak of solid coal is lower than the conventional panel, and the width of the limit equilibrium zone is also reduced by a small percentage. After the narrow coal pillar gob-side entry has been excavated, the peak stress in solid coal increases, and the width of the limit equilibrium zone decreases, so the practical stress concentration increases. However, the NCPG located in areas of lower stress. The peak stress in solid coal of the NCPG does not increase, but the width of the limit equilibrium zone increases, so the practical stress concentration decreases. NCPC makes the concentrated stress transfer into the deep coal body and plays the role of pressure avoidance. Compared with the narrow coal pillar gob-side entry, the NCPG reduces the energy stored in coal and rock masses and increases the energy consumption. It has significantly improved the regionality, initiative, safety, and timeliness of rock burst prevention in deep high-stress coal seam mining.